Experience with the use of a first-line regimen of stavudine, lamivudine and nevirapine in patients in the TREAT Asia HIV observational Database - Zhou, J.; Paton, N.I.; Ditangco, R.; Chen, Y.M.; Kamarulzaman, A.; Kumarasamy, N.; Lee, C.K.C.; Li, P.C.K.; Merati, T.P.; Phanuphak, P.; Pujari, S.; Vibhagool, A.; et al. (2007)
Background The antiretroviral treatment (ART) combination of stavudine, lamivudine and nevirapine (d4T/3TC/NVP) is the most frequently used initial regimen in many Asian countries. There are few data on the outcome of this treatment in clinic cohorts in this region. Methods We selected patients from the TREAT Asia HIV Observational Database (TAHOD) who started their first ART regimen with d4T/3TC/NVP. Treatment change was defined as cessation of therapy or the addition or change of one or more drugs. Clinical failure was defined as diagnosis with an AIDS-defining illness, or death while on d4T/3TC/NVP treatment. Results The rate of treatment change among TAHOD patients starting d4T/3TC/NVP as their first antiretroviral treatment was 22.3 per 100 person-years, with lower baseline haemoglobin (i.e. anaemia) associated with slower rate of treatment change. The rate of clinical failure while on d4T/3TC/NVP treatment was 7.3 per 100 person-years, with baseline CD4 cell count significantly associated with clinical failure. After d4T/3TC/NVP was stopped, nearly 40 of patients did not restart any treatment and, of those who changed to other treatment, the majority changed to zidovudine (ZDV)/3TC/NVP and less than 3 of patients changed to a protease inhibitor (PI)-containing regimen. The rates of disease progression on the second-line regimen were similar to those on the first-line regimen. Conclusion These real-life data provide an insight into clinical practice in Asia and the Pacific region. d4T/3TC/NVP is maintained longer than other first-line regimens and change is mainly as a result of adverse effects rather than clinical failure. There is a need to develop affordable second-line antiretroviral treatment options for patients with HIV infection in developing countries.